The Effect Of Good Corporate Governance And Company Size On Financial Performance With Audit Quality As A Moderating Variable In LQ45 Companies - M Haikal Firdaus; Syaiful Rahman Soenaria; Anies Lastiati (UNIVED Press, 2025)
The study aims to examine the effect of Good Corporate Governance (GCG) and company size on financial performance with audit quality as a moderating variable in companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) during 2021-2023. Using a quantitative approach, the study also applied multiple linear regression analysis and Moderated Regression Analysis (MRA) to test the relationship between variables. The research conducted shows that GCG, as measured by independent commissioners and managerial ownership, has a positive influence on financial performance. Audit quality is proven to moderate the relationship between GCG and financial performance, strengthening the positive influence of GCG on firm performance. These findings make a significant contribution to the development of agency and stakeholder theory, and provide practical recommendations for companies to improve governance and audit quality to improve financial performance. This study also observes research gaps related to the implementation of GCG in Indonesia which is lagging when compared to other ASEAN countries, as well as the need for stricter supervision in the management of companies listed on the IDX.